Teaching young adult learners is an intelligent orchestration of science and arts. Issue 1 (27th October 2020) - Namhata, Rima; Ghosh, Vinit
Abstract : Purpose: This paper aims to propose a classroom teaching orchestration technique, analogically drawing a reference from the movie, Prestige (2006). The generation of post-millennials has shorter attention span and motivation and prefers a learner-centric teaching style. This paper attempts to mitigate such challenges by bringing an analogy with a magic trick along with proposing a "divergent-convergent diamond structure" to anchor and synthesise teaching deliverables for the learners. Design/methodology/approach: This is a practitioner's study where practical experiences of the authors have led to the conceptualisation of the central theme discussed. Findings: From a practitioner's opinion and interpretation, the proposed "divergent-convergent diamond structure" has the potential to make postgraduate classes more engaging. The proposed structure may suggestively promote self-efficacy, trigger curious minds, bring relevance, indulge participatory learning and consolidate the concepts.